The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/jfm-08-2021-0081
|View full text |Cite
|
Sign up to set email alerts
|

A review of research in activity-based working over the last ten years: lessons for the post-COVID workplace

Abstract: Purpose The purpose of this paper is to map and describe findings from research conducted in workspaces designed to support activity-based working (ABW) over the past 10 years (2010–2020) with a view of informing post-COVID workplaces of the positive and negative attributes of ABW. Design/methodology/approach Scopus was used as the search engine for this review. Papers which reported findings related to ABW and performed field study in ABW workspaces with adult occupants were included. Out of the 442 initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 43 publications
4
35
1
Order By: Relevance
“…In addition, the COVID-19 pandemic has pushed many workers away from their offices and into their homes. It can be assumed that this hybrid way of working will prompt organisations to adjust their offices more into activity-based working (ABW) [ 22 ]. However, in the decision-making process about whether ABW should be introduced, the challenges raised by Marzban and colleagues such as unclear rules and policies for flexible working, lack of support for IT facilities, a weak management system, and difficulties concerning communication between subordinates and employers, also need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the COVID-19 pandemic has pushed many workers away from their offices and into their homes. It can be assumed that this hybrid way of working will prompt organisations to adjust their offices more into activity-based working (ABW) [ 22 ]. However, in the decision-making process about whether ABW should be introduced, the challenges raised by Marzban and colleagues such as unclear rules and policies for flexible working, lack of support for IT facilities, a weak management system, and difficulties concerning communication between subordinates and employers, also need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Three key components are important when implementing AFOs: physical environment, organisation aspects, and human perspectives. For a successful implementation of AFOs, a holistic approach is needed where subordinates are committed to the change and have flexibility to choose how and where to work, and to create a satisfactory physical and psychosocial work environment [ 22 ]. One study has also indicated that it is important that during the implementation of an AFO the manager is perceived to have change-oriented leadership behaviours to avoid productivity loss among employees [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such arrangements have been found to lead to increased employee satisfaction in an experiment in China [37] and in a U.K. survey [38]. A review on activity-based work (ABW) found mixed views from workers on the overall experience of working in ABWsupportive environments, but a positive to mixed associations between ABW and job satisfaction, work condition and organizational commitment [39]. Benefits for occupants include increasing overall comfort, choice, and control [40] as well as access to an inspiring work environment [41].…”
Section: Hybrid and Flexible Work Arrangementsmentioning
confidence: 99%
“…Given that the push for workspace flexibility precedes the pandemic, remote working arrangements are expected to continue even after the pandemic. There has been a trend towards reducing floor area per person, and many organizations were already implementing shared workspaces [35,36], due to the positive cost-benefits to organizations from a reduced office footprint [39]. 25% of workers in high-income countries are expected to continue remote working either part-time or full-time after the pandemic [42], and the aforementioned survey of U.S. adults found that 54% of employees would want to work from home all or most of the time after the pandemic [43].…”
Section: Hybrid and Flexible Work Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation